Efficacy and safety of PD-1/PD-L1 inhibitor combined with chemotherapy versus chemotherapy alone in the treatment of advanced gastric or gastroesophageal junction adenocarcinoma: a systematic review and meta-analysis - Liu, Bo-Wei; Shang, Qi-Xing; Yang, Yu-Shang; Chen, Long-Qi (Frontiers in Oncology, 2023)
Background:There is increasing evidence that immunotherapy(PD-1 inhibitor) combined with chemotherapy is superior to chemotherapy alone in neoadjuvant therapy for patients with previously untreated, unresectable advanced or metastatic Esophageal adenocarcinoma(EAC)/Gastric/Gastroesophageal junction adenocarcinoma (GEA).However,recent studies have been in conflict.Therefore, the aim of this article is to evaluate the efficacy and safety of PD-1 inhibitors combined with chemotherapy in neoadjuvant therapy through meta-analysis. Method：We comprehensively reviewed literature and clinical RCTs by February 2022 through searching MESH headings and keyword such as ‘esophageal adenocarcinoma’ or ‘immunotherapy’ on several databases, including EmBase, Cochrane, Pubmed, and clinical.gov website. Two authors independently selected studies, extracted data and assessed risk of bias and quality of evidence using standardised Cochrane Methods procedures.The primary outcome was 1-year overall survival (OS),1-year progression-free survival (PFS), estimated by calculating the 95% confidence interval for the combined odds ratio（OR）value and hazard ratio(HR). Secondary outcomes estimated using OR were disease objective response rate (DOR) and incidence of adverse events. Results: Four RCTs with a total of 3013 patients on researching the efficacy of immunotherapy plus chemotherapy versus chemotherapy on gastrointestinal cancer were included in this meta-analysis. The result of patients who did not accept surgery received immontherapy plus chemotherapy shows that PFS(HR=0.74,[95%CI 0.67-0.82];p<0.001),OS (HR=0.80 [95%CI: 0.73-0.89]; p<0.001)and DOR(RR=1.37 [95%CI 1.11-1.70];p=0.004) have significant advantages when compared to patients received chemotherapy alone .However,immunotherapy combined with chemotherapy increased the incidence of adverse reactions such as alanine aminotransferase elevation(OR=1.55 95%CI 1.17-2.07)and Palmar-plantar erythrodysaesthesia(PPE) syndrome(OR=1.30 95%CI 1.05-1.63). Meanwhile, for patients with combined positive score(CPS)score equal to 1 or greater than 1 , immunotherapy combined with chemotherapy bring ideal results in improving the OS rate(HR=0.81,[95%CI 0.73-0.90];p=0.0001). Conclusion：Our study shows that there‘s obvious benefit will immunotherapy plus chemotherapy bring to patients with previously untreated, unresectable advanced or metastatic Esophageal adenocarcinoma(EAC)/Gastric/Gastroesophageal junction adenocarcinoma (GEA) when compared with chemotherapy alone,However, high risk of adverse reactions may happen during immunotherapy plus chemotherapy, and more studies focusing on the treatment strategies of untreated, unresectable advanced or metastatic Esophageal adenocarcinoma(EAC)/Gastric/Gastroesophageal junction adenocarcinoma (GEA) are warranted